2013
DOI: 10.1016/j.chembiol.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine and Piperidine Triazole Ureas as Ultrapotent and Highly Selective Inhibitors of Monoacylglycerol Lipase

Abstract: Monoacylglycerol lipase (MAGL) terminates the signaling function of the endocannabinoid, 2-arachidonoylglycerol (2-AG). During 2-AG hydrolysis, MAGL liberates arachidonic acid, feeding the principal substrate for the neuroinflammatory prostaglandins. In cancer cells, MAGL redirects lipid stores toward protumorigenic signaling lipids. Thus MAGL inhibitors may have great therapeutic potential. Although potent and increasingly selective MAGL inhibitors have been described, their number is still limited. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
135
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(139 citation statements)
references
References 38 publications
4
135
0
Order By: Relevance
“…When studying the mechanism of action of irreversible MGL inhibitors, we applied the concept advanced by Aaltonen and coworkers 16 according to whom the effects of the leaving group are strictly dependent upon its physicochemical properties, although steric hindrance may also play a role. In fact, we found that the effect on potency seems to be related to the pK a of the leaving group's conjugated acid (ideal pK a ∼ 10).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When studying the mechanism of action of irreversible MGL inhibitors, we applied the concept advanced by Aaltonen and coworkers 16 according to whom the effects of the leaving group are strictly dependent upon its physicochemical properties, although steric hindrance may also play a role. In fact, we found that the effect on potency seems to be related to the pK a of the leaving group's conjugated acid (ideal pK a ∼ 10).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Crude title compound was used in the following step without any further purification (1.02 g, 81% yield). 1 3,4-Dihydro-2H-benzo [4,5]thiazolo[3,2-a]pyrimidine (16). To a stirred solution of alcohol 15 (1.02 g, 4.90 mmol) in dry dichloromethane (50.0 mL) cooled to 0°C, TEA (2.05 mL, 14.70 mmol) and mesyl chloride (570 μL, 7.35 mmol) were added and the mixture was stirred at 25°C under Ar atmosphere for 1.5 h. Methanol (300 μL) was added to quench the excess of mesyl chloride, and the reaction was treated with a further amount of TEA (2.05 mL, 14.70 mmol) and stirred at 50°C for 1.5 h. Water was added, and the aqueous phase was extracted with dichloromethane (3 × 15.0 mL).…”
Section: Trans-4-(34-dimethoxyphenyl)-3-(4-methoxyphenyl)-1-(piperidmentioning
confidence: 99%
See 1 more Smart Citation
“…153 Furthermore, compounds 146 (JJKK-046) and 147 (JJKK-048) ( Figure 54) were determined to inhibit hMAGL in the subnanomolar range (IC50 = 0.562 and 0.363 nM, respectively) and exert appreciable selectivity over several serine hydrolases, as shown using ABPP assays, including FAAH (SI > 1200 and 11200 fold, respectively), ABHD6 (SI > 150 and 600 fold, respectively). In addition, these two compounds exhibited no detectable potency against ABHD12 at a 1 μM concentration.…”
mentioning
confidence: 99%
“…152 Recently, a series of piperazine/piperidine triazole ureas were described as highly selective MAGL inhibitors. 153 Structureactivity relationships illustrated that the Y-type scaffold of triazole ureas favors selectivity over FAAH.…”
mentioning
confidence: 99%